2015
DOI: 10.1177/0018720815607317
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Input Hardware and Work Surface Angle on Upper Limb Posture in a Hybrid Computer Workstation

Abstract: Objective:We evaluated the effect of work surface angle and input hardware on upper-limb posture when using a hybrid computer workstation.Background: Offices use sit-stand and/or tablet workstations to increase worker mobility. These workstations may have negative effects on upper-limb joints by increasing time spent in non-neutral postures, but a hybrid standing workstation may improve working postures.Method: Fourteen participants completed office tasks in four workstation configurations: a horizontal or slo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 28 publications
(44 reference statements)
0
8
0
Order By: Relevance
“…Postures and muscle activity of the distal upper extremities were also dependent on the types of devices, with generally greater non-neutral postures, but lower muscle activity at the level of the wrist, elbow, fingers and/or thumb found during use of MTSD compared to traditional electronic devices. There was more wrist extension [ 16 , 20 ], wrist pronation and elbow flexion [ 48 ] during the use of a smartphone or tablet compared to a laptop or physical keypad phone. Several studies reported similar findings of lower muscle activities at wrist and finger flexors and extensors [ 16 , 20 – 22 ] and thumb abductors [ 20 , 22 ] when using a smartphone or tablet compared to a laptop, netbook or physical keypad phone, and when using a virtual compared to physical keyboard [ 18 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Postures and muscle activity of the distal upper extremities were also dependent on the types of devices, with generally greater non-neutral postures, but lower muscle activity at the level of the wrist, elbow, fingers and/or thumb found during use of MTSD compared to traditional electronic devices. There was more wrist extension [ 16 , 20 ], wrist pronation and elbow flexion [ 48 ] during the use of a smartphone or tablet compared to a laptop or physical keypad phone. Several studies reported similar findings of lower muscle activities at wrist and finger flexors and extensors [ 16 , 20 – 22 ] and thumb abductors [ 20 , 22 ] when using a smartphone or tablet compared to a laptop, netbook or physical keypad phone, and when using a virtual compared to physical keyboard [ 18 ].…”
Section: Resultsmentioning
confidence: 99%
“…The authors of the latter study did not standardize duration for each of the tasks, which may have affected the accuracy of findings. At the distal upper extremities, greater wrist pronation and ulnar deviation [ 48 , 68 ], as well as greater muscle activity of finger flexors [ 35 , 55 ] and wrist extensors and flexors [ 68 ], were found during active tasks compared to passive tasks.…”
Section: Resultsmentioning
confidence: 99%
“…This result was also verified by Lin et al (2015), who showed that pro-longed touch-typing affects the upper extremities and neck. Also, Kingston et al (2016) pointed out that reading tasks performed using tablet computers affected wrist, elbow, and shoulder.…”
Section: Discussionmentioning
confidence: 99%
“…All studies were quite small, including 1 to 20 participants. Five studies were conducted in laboratory or simulated the work situation in laboratory environment (Seaman et al,2010;Antonio Diego-Mas et al,2014;Bataller-Cervero et al, 2016;Hwang et al, 2016;Valero et al, 2016) and just two of them (Botter et al, 2013(Botter et al, , 2016Kingston et al, 2015) specifically were oriented to study computer workers in real time. In order to investigate the posture analysis in different situation and for different goals, various body parts were analyzed, in each study the subjects were asked to perform specific movements: flexionextension, abduction/adduction and lateral bending.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, Kingston et al (2016) also evaluated the effect of work surface on upper-limb posture with Optoelectric motion analysis system for computer workers. Three-dimensional upper-limb postures were recorded during three tasks: reading, form filling, and writing e-mails (Kingston et al, 2015).…”
Section: Introductionmentioning
confidence: 99%